Struktur Tata Kelola Perusahaan dan Team-Centric Culture terhadap Pengungkapan Sustainability Report pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Zahrotun Maulidah; Putu Prima Wulandari (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the effect of corporate governance structure and team-centric culture on sustainability report disclosure in energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This study uses a quantitative method with secondary data obtained from companies’ financial reports and sustainability reports. The sample was selected using a purposive sampling method, resulting in 66 research observations. Corporate governance structure is measured through the number of board of directors, board of commissioners, and audit committee members, while team-centric culture is measured using the ratio of employee compensation to operating expenses. Sustainability report disclosure is measured using the Sustainability Report Disclosure Index (SRDI) and analyzed using panel data regression with the assistance of EViews 12 software. The results show that the board of commissioners has a positive and significant effect on sustainability report disclosure, while the board of directors, audit committee, and team-centric culture have no significant effect on sustainability report disclosure.